PHYSICAL AND MECHANICAL CHARACTERIZATION OF AL-SI ALLOYS WITH THE ADDITION OF MG AS MATERIAL OF THE CHASSIS MODEL MADE BY THE HIGH-PRESSURE DIE-CASTING (HPDC) - Bayuseno, Athanasius Priharyoto; Kelana, Akhmad Ibrahim Jayeng; Agusta, Dedas (ROTASI, 2016)
Aluminium alloys have been developed for the automotive material, especially in the chassis structure. One of the development of aluminum alloy focuses on the system of Al-Mg-Si. This paper presents results on a manufacturing chassis car model made by Al-Si alloys with variety of magnesium content through the HPDC process. In this study, the selected raw material is ADC12, while HPDC was performed at a constant pressure of 7 MPa. The optimal composition of a super ductile alloy of Al-Mg-Si was related to the Mg variation in wt.%; 0, 3, 4 and 5 and the pouring temperature of 750 OC. The heat treatment was performed at the age hardening treatment at 540Â OC for 60 minutes and artificial aging of 150Â OC for 4 hours. Material characterization includes porosity, hardness testing and micro structure evaluation using an optical microscope. The measured data of porosity, hardness, tensile strength were compared to that of standard data for automotive chassis material. It shows that the measured hardness met the required standard of automotive material